Bhoṃsalā Vedaśāstra Mahāvidyālaya, amrta mahotsava, smāraka grantha = Commemoration volume - Hardas, Balshastri, 1918-1968 (Bhoṃsalā Vedaśāstra Mahāvidyālaya, 1960)
Contributed articles on Hinduism and Indic philosophy.